Electrode material resistivity measurement method and battery slurry homogenization process screening method
Patent Information
- Application Number
- CN202611000738.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-06
- Publication Date
- 2026-10-23
AI Technical Summary
[0049]上述电极材料电阻率测量方法及电池浆料匀浆工艺筛选方法,通过将浆料涂覆层直接设于箔材表面,能够更真实地模拟极片制备工艺,为提高电阻率测试结果的可靠性奠定了基础;在此基础上,通过将中空取样管压入浆料涂覆层,获得嵌有中空取样管的浆料涂覆层;进而对嵌有中空取样管的浆料涂覆层进行烘干处理,能够使中空取样管内的浆料涂覆层固化并从箔材表面脱离,得到完整的电极材料样品,此过程无需借助任何外力,避免了强制剥离导致的电极材料样品断裂、边界破损等问题,实现了电极材料样品的自然脱离,整个过程不存在机械损伤风险,保证了电极材料样品的完整性;进而基于完整的电极材料样品进行电阻率测量,有效提高了测试结果的准确性和可靠性。
Smart Images

Figure CN122962286A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of battery technology, and in particular to a method for measuring the resistivity of electrode materials and a method for screening battery slurry homogenization processes. Background Technology
[0002] As market demand for batteries with high energy density, long cycle life, and high safety continues to grow, battery manufacturing is placing higher demands on the precision of control over key processes.
[0003] Battery electrodes consist of foil and electrode materials disposed on the surface of the foil. The resistivity of the electrode materials is a key parameter affecting the battery's internal resistance, charge / discharge efficiency, and consistency. Therefore, accurately measuring the resistivity of the electrode materials is of great significance for ensuring battery performance consistency and improving production yield. Summary of the Invention
[0004] Currently, the integrity of electrode material samples prepared by traditional methods is difficult to guarantee. Sample defects introduce additional contact resistance and measurement errors, making it impossible for test results to truly reflect the intrinsic electrical characteristics of the electrode material, thus seriously affecting the accuracy and reliability of the test results. Therefore, it is necessary to provide a method for measuring the resistivity of electrode materials and a method for screening battery slurry homogenization processes to address the above-mentioned technical problems.
[0005] In a first aspect, this application provides a method for measuring the resistivity of an electrode material, the method comprising:
[0006] S100: Obtain a paste coating layer on the surface of the foil;
[0007] S200. Press the hollow sampling tube into the slurry coating layer to obtain a slurry coating layer with the hollow sampling tube embedded.
[0008] S300. The slurry coating layer embedded with the hollow sampling tube is dried to solidify the slurry coating layer inside the hollow sampling tube and detach it from the surface of the foil to obtain an electrode material sample.
[0009] S400. Based on the electrode material sample, the resistivity of the electrode material is measured to obtain the resistivity test results.
[0010] In one embodiment, S100 specifically includes:
[0011] S110. Obtain the slurry; the slurry is prepared by a preset homogenization process;
[0012] S120. The slurry is coated onto the surface of the foil to form the slurry coating layer on the surface of the foil.
[0013] In one embodiment, S120 specifically includes:
[0014] S121. Determine a foil material that matches the polarity of the slurry, and lay the foil material flat on the panel;
[0015] S122. The slurry is coated onto the surface of the foil to form a slurry coating layer on the surface of the foil with a thickness equal to a preset coating thickness; the preset coating thickness is 3000μm~7000μm.
[0016] In one embodiment, S200 specifically includes:
[0017] The hollow sampling tube is pressed into the slurry coating layer at a preset pressing speed and preset pressing angle until the hollow sampling tube contacts the surface of the foil.
[0018] In one embodiment, when the initial solid content of the slurry coating is greater than or equal to 50%, step S300, the drying process of the slurry coating with the embedded hollow sampling tube, includes:
[0019] Under a preset drying environment, the slurry coating layer with the hollow sampling tube is pre-dried for a first preset time using a first drying temperature.
[0020] The first drying temperature is raised to a second drying temperature, and the pre-dried slurry coating layer containing the hollow sampling tube is dried using the second drying temperature until the slurry coating layer inside the hollow sampling tube is cured.
[0021] In one embodiment, when the initial solid content of the slurry coating is less than 50%, S200 specifically includes:
[0022] Under a preset drying environment, the slurry coating layer is pre-dried for a second preset time using a third drying temperature to obtain a pre-dried slurry coating layer.
[0023] The hollow sampling tube is pressed into the pre-dried slurry coating layer until the hollow sampling tube contacts the surface of the foil.
[0024] In one embodiment, step S300, drying the slurry coating layer embedded with the hollow sampling tube, includes:
[0025] Under a preset drying environment, the slurry coating layer with the hollow sampling tube is dried using a fourth drying temperature until the slurry coating layer inside the hollow sampling tube is cured.
[0026] The fourth drying temperature is higher than the third drying temperature.
[0027] In one embodiment, S300 specifically includes:
[0028] The slurry coating layer with the embedded hollow sampling tube is dried.
[0029] The dried slurry coating layer containing the hollow sampling tube is cooled to a preset temperature.
[0030] The slurry coating layer located inside the hollow sampling tube is peeled off from the surface of the foil to obtain the electrode material sample.
[0031] In one embodiment, S400 specifically includes:
[0032] A preset pressure is applied to the electrode material sample, and the resistivity of the electrode material sample during the compression process is measured simultaneously to obtain the resistivity test result; the resistivity test result includes the corresponding relationship between the resistivity of the electrode material sample and the pressure.
[0033] Alternatively, the S400 specifically includes:
[0034] A preset pressure is applied to the electrode material sample to obtain a compacted sample;
[0035] The resistivity of the compacted sample is measured to obtain the resistivity test result; the resistivity test result includes the resistivity of the compacted sample.
[0036] In one embodiment, the hollow sampling tube is made of quartz; and / or,
[0037] The wall thickness of the hollow sampling tube is 0.1 mm to 1 mm; and / or,
[0038] The height of the hollow sampling tube is 16mm~32mm; and / or,
[0039] The hollow sampling tube has a press-in end, and the hollow sampling tube has a chamfer at the press-in end.
[0040] In one embodiment, the hollow sampling tube is a cylindrical structure with open ends. The hollow sampling tube has axial and circumferential directions. The tube wall of the hollow sampling tube is provided with a through-hole area. Multiple through holes are provided in the through-hole area. The multiple through holes are evenly spaced in multiple rows along the axial direction of the hollow sampling tube, and the through holes in each row are evenly spaced along the circumferential direction of the hollow sampling tube.
[0041] The hollow sampling tube has a pressing end for pressing into the slurry coating layer, and the distance between the through-hole area and the pressing end is greater than the thickness of the slurry coating layer.
[0042] In one embodiment, the average diameter of the plurality of through holes is 0.2 mm to 0.3 mm; and / or,
[0043] The inner wall of the hollow sampling tube has an area of S1 where the through hole is provided and an area of S2 where the through hole is not provided, where 0.1≤S1 / (S1+S2)≤0.7.
[0044] Secondly, this application provides a method for screening battery slurry homogenization processes, the method comprising:
[0045] Various slurries to be tested were prepared using different homogenization processes;
[0046] For each of the slurries to be tested, the resistivity measurement method of the electrode material described above is used to obtain the resistivity test results corresponding to the slurry to be tested;
[0047] The optimal resistivity test result that meets the preset screening conditions is determined from multiple resistivity test results;
[0048] The homogenization process corresponding to the optimal resistivity test result is determined as the optimal homogenization process.
[0049] The aforementioned method for measuring the resistivity of electrode materials and the method for screening battery slurry homogenization processes, by directly applying the slurry coating layer to the foil surface, can more realistically simulate the electrode preparation process, laying the foundation for improving the reliability of resistivity test results. Furthermore, by pressing a hollow sampling tube into the slurry coating layer, a slurry coating layer with an embedded hollow sampling tube is obtained. Then, drying the slurry coating layer with the embedded hollow sampling tube allows the slurry coating layer inside the hollow sampling tube to solidify and detach from the foil surface, obtaining a complete electrode material sample. This process requires no external force, avoiding problems such as electrode material sample breakage and boundary damage caused by forced peeling, achieving natural detachment of the electrode material sample. The entire process has no risk of mechanical damage, ensuring the integrity of the electrode material sample. Therefore, resistivity measurement based on the complete electrode material sample effectively improves the accuracy and reliability of the test results. Attached Figure Description
[0050] To more clearly illustrate the technical solutions in the embodiments of this application or related technologies, the drawings used in the description of the embodiments of this application or related technologies will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.
[0051] Figure 1 This is a flowchart illustrating a method for measuring the resistivity of electrode materials in one embodiment;
[0052] Figure 2 This is a schematic diagram of the force applied at a point on the slurry coating layer inside the hollow sampling tube during the drying stage in one embodiment.
[0053] Figure 3 This is a schematic flowchart of the slurry coating layer coating step in one embodiment;
[0054] Figure 4 This is a flowchart illustrating the slurry coating layer coating step in another embodiment;
[0055] Figure 5 This is a schematic diagram of the force applied at a point on the slurry coating layer inside the hollow sampling tube during the coating stage in another embodiment.
[0056] Figure 6 This is a schematic diagram of the stress on the slurry coating during the peeling stage in another embodiment;
[0057] Figure 7 This is a schematic diagram of a hollow sampling tube in one embodiment;
[0058] Figure 8 This is a schematic diagram illustrating the relationship between the resistivity of an electrode material sample and pressure in a specific embodiment. Detailed Implementation
[0059] To make the objectives, technical solutions, and advantages of this application clearer, the following detailed description is provided in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of this application.
[0060] Electrode slurry preparation is a core step in battery electrode manufacturing. The slurry is coated onto the surface of a current collector (such as copper foil or aluminum foil), and after drying and compaction, it forms the battery electrode. Taking lithium batteries as an example, the active material layer of its electrode (formed by drying and compacting the electrode slurry onto the surface of the current collector) is the main region for lithium-ion insertion / extraction reactions, and the resistivity of the active material layer plays a decisive role in the gain and loss of electrons by lithium ions.
[0061] In the slurry preparation process, one of the core objectives of the homogenization step is to uniformly disperse the conductive agent between the positive and negative electrode main material particles, constructing an efficient electronic conduction network to reduce the internal resistance of the battery during charging and discharging. The quality of this electronic conduction network directly affects the resistivity of the active material layer. Therefore, accurately measuring the resistivity of the active material layer of the battery electrode after drying and compaction is of great significance for ensuring battery performance consistency and improving production yield.
[0062] Related technologies propose methods for directly testing the resistivity of wet slurry (hereinafter referred to as the wet method). However, wet slurry, without drying and compaction, cannot accurately characterize the final performance of the dried and compacted active material layer in the finished battery. On the one hand, some solvents in the formulation will evaporate during the drying process, resulting in a discrepancy between the actual composition and the test conditions. On the other hand, wet slurry is not a homogeneous solution but a suspension, which has problems such as sedimentation and uneven dispersion. In addition, the slurry contains a large amount of solvent and adhesive (most of which are non-conductive), resulting in excessively large gaps between material particles, insufficient contact between particles, and the inability to fully utilize the performance of the main material and conductive agent, thus making it impossible to accurately measure the resistivity of the electrode material (i.e., the positive / negative electrode active material layer).
[0063] Another related technology involves measuring resistivity by preparing electrode material samples in a laboratory environment. However, due to the difficulty in ensuring sample integrity through the preparation method, the test results cannot truly reflect the intrinsic electrical characteristics of the electrode material, thus seriously affecting the accuracy and reliability of the test results.
[0064] Therefore, this application provides a method for measuring the resistivity of electrode materials, which aims to improve the accuracy of resistivity measurement by preparing electrode material samples with high integrity, thereby guiding cell development and process development.
[0065] The resistivity measurement method for electrode materials provided in the embodiments of this application is described in detail below.
[0066] In one embodiment, such as Figure 1 As shown, Figure 1 This is a flowchart illustrating a method for measuring the resistivity of an electrode material in one embodiment; the method for measuring the resistivity of an electrode material includes the following steps:
[0067] S100: Obtain a slurry coating layer on the surface of the foil.
[0068] The slurry coating layer refers to the liquid film layer formed by coating the slurry onto the surface of the foil. Depending on the polarity, the slurry coating layer can be a positive electrode slurry coating layer or a negative electrode slurry coating layer. Slurry refers to a liquid mixture, which may include, but is not limited to, electrode active materials (positive or negative electrode), conductive agents, binders, and solvents. It is understood that the slurry can be a positive electrode slurry or a negative electrode slurry, and the specific type is related to the polarity of the electrode active material. For example, the main components of graphite-based negative electrode slurries include graphite (usually accounting for more than 90%), binders (such as polyvinylidene fluoride / styrene-butadiene rubber, carboxymethyl cellulose / polyacrylic acid, etc.), and conductive agents (such as carbon black, graphite, carbon nanotubes, graphene, carbon nanofibers, etc.); the main components of ternary material positive electrode slurries include lithium nickel cobalt manganese oxide (usually accounting for more than 90%), binders (such as polyvinylidene fluoride / styrene-butadiene rubber, carboxymethyl cellulose / polyacrylic acid, etc.), and conductive agents (such as carbon black, graphite, carbon nanotubes, graphene, carbon nanofibers, etc.).
[0069] Foil material refers to a current collector with polarity matched to the slurry, used to support the slurry coating layer and simulate the current collector environment in the actual electrode fabrication process. For example, the foil material can be copper foil, aluminum foil, or nickel foil. It should be noted that traditional techniques typically use auxiliary methods such as plastic wrap or insulating coatings to prepare samples. However, this application directly coats the slurry coating layer onto the foil surface, maximizing the preservation of the original characteristics of the slurry and avoiding interference and contamination from external media. This ensures that the resistivity test results accurately reflect the true electrical properties of the electrode material.
[0070] In some embodiments, the method for obtaining a slurry coating layer on the surface of a foil may be: uniformly coating the slurry onto the surface of the foil using a doctor blade or other coating processes to form the desired slurry coating layer.
[0071] S200. Press the hollow sampling tube into the slurry coating layer to obtain a slurry coating layer with the hollow sampling tube embedded.
[0072] The hollow sampling tube may, but is not limited to, be a cylindrical structure open at both ends. The inner cavity of the hollow sampling tube accommodates and constrains the deformation of the slurry coating layer during the drying process, provides physical support when the slurry is not fully cured, and guides the slurry to naturally peel off from the foil interface during dehydration and shrinkage. In some possible embodiments, the hollow sampling tube may, but is limited to, being made of materials such as ceramics, polymers, or glass; no specific limitations are made here.
[0073] In an exemplary embodiment, the method for pressing the hollow sampling tube into the slurry coating layer can be as follows: before the slurry is completely dried, pressure is applied to the hollow sampling tube to allow it to penetrate the slurry coating layer to the surface of the contact foil, thereby obtaining a slurry coating layer with the hollow sampling tube embedded within it. The method for pressing the hollow sampling tube in can be, but is not limited to, applying uniform pressure using a special press to ensure that the slurry coating layer fully fills the inner cavity of the hollow sampling tube and that the hollow sampling tube makes stable contact with the foil surface.
[0074] Understandably, after the hollow sampling tube is embedded in the slurry coating layer, the slurry coating layer will generate a wrapping force and friction on the outer wall of the hollow sampling tube, so that the hollow sampling tube can be stably embedded in the slurry coating layer after being pressed in, without the need for any external force for support.
[0075] S300. The slurry coating layer embedded with the hollow sampling tube is dried to solidify the slurry coating layer inside the hollow sampling tube and detach it from the surface of the foil to obtain an electrode material sample.
[0076] It should be noted that after the hollow sampling tube is embedded in the slurry coating, the slurry coating will adhere to the tube wall. Initially, the tube wall provides inward support to the slurry coating, maintaining the stability of the slurry's shape; during the later drying process, please refer to... Figure 2 ( Figure 2 In the diagram, 10 represents foil, 11 represents hollow sampling tube, and 12 represents slurry coating layer. The wall of the hollow sampling tube 11 exerts a radial pulling force (F) on the slurry coating layer 12 inside the tube towards the tube wall. 牵引 The traction force and the internal shrinkage stress of the slurry (ΣF) 应力 The combined effect of these factors makes the slurry coating layer 12 inside the hollow sampling tube 11 more regular during the drying and molding process. The shrinkage stress can be understood as the force exerted by the binder on the slurry particles during shrinkage as the solvent in the slurry coating layer 12 evaporates. The resultant force of the radial traction force and the shrinkage stress (F) 合 The coating layer 12 generally faces away from the interface at the adhesion interface between the slurry coating layer 12 and the foil 10, which helps promote interface separation. It should be noted that... Figure 2 This is only used to explain the stress situation at a certain point on the interface of the slurry coating layer 12 inside the hollow sampling tube 11, and the complete slurry coating layer outside the hollow sampling tube is not shown.
[0077] This application involves embedding a hollow sampling tube into the slurry coating layer before the slurry coating layer is completely dried, and then drying the slurry coating layer containing the hollow sampling tube as a whole. This allows the slurry coating layer inside the hollow sampling tube to naturally detach from the foil during the drying process without the need for any external force, thereby obtaining a complete electrode material sample.
[0078] S400: Based on the electrode material sample, the resistivity of the electrode material is measured to obtain the resistivity test results.
[0079] The resistivity measurement of electrode materials may be performed using, but is not limited to, the four-probe method, the two-probe method, the van der Burg method, or other resistivity testing methods known in the art. No specific testing method is limited here.
[0080] The resistivity test results may include the relationship between the resistivity of the electrode material sample and pressure, and / or the resistivity of the compacted sample. The relationship between the resistivity of the electrode material sample and pressure characterizes the resistivity change characteristics of the electrode material sample under different pressures; the resistivity of the compacted sample refers to the resistivity value of the electrode material sample under a specific compaction state.
[0081] It should be noted that the electrode material samples obtained through the above steps S100 to S300 have only undergone drying treatment and have not undergone compaction treatment. Therefore, it is still necessary to compact the electrode material samples.
[0082] In some embodiments, the resistivity measurement of the electrode material can be performed simultaneously with the compaction process to obtain the corresponding relationship between the resistivity of the electrode material sample and the pressure. At the same time, the resistivity of the compacted sample can also be obtained at the end of the compaction process. In other embodiments, the resistivity of the electrode material can be measured after the electrode material sample is compacted to obtain the resistivity of the compacted sample. The choice can be made according to the actual measurement requirements and is not specifically limited here.
[0083] The electrode material resistivity measurement method provided in the above embodiments, by directly applying the slurry coating layer to the foil surface, can more realistically simulate the electrode preparation process, laying the foundation for improving the reliability of resistivity test results. Furthermore, by pressing a hollow sampling tube into the slurry coating layer, a slurry coating layer with an embedded hollow sampling tube is obtained. Then, drying the slurry coating layer with the embedded hollow sampling tube allows the slurry coating layer inside the hollow sampling tube to solidify and detach from the foil surface, obtaining a complete electrode material sample. This process requires no external force, avoiding problems such as electrode material sample breakage and boundary damage caused by forced peeling, achieving natural detachment of the electrode material sample. The entire process has no risk of mechanical damage, ensuring the integrity of the electrode material sample. Therefore, resistivity measurement based on the complete electrode material sample effectively improves the accuracy and reliability of the test results.
[0084] In one embodiment, such as Figure 3 As shown, Figure 3 This is a flowchart illustrating the slurry coating layer coating step in one embodiment; based on the above embodiment, S100 obtains a slurry coating layer on the surface of the foil, specifically including the following steps:
[0085] S110, Obtain the slurry.
[0086] The slurry is prepared through a preset homogenization process. The preset homogenization process can be a homogenization process to be evaluated. It is used to verify the quality of the preset homogenization process through the electrode material resistivity measurement method of this application, so as to identify unqualified products in the homogenization stage and prevent them from flowing to the downstream process.
[0087] S120. Apply the slurry to the surface of the foil to form a slurry coating layer on the surface of the foil.
[0088] In some embodiments, a slurry can be uniformly applied to the surface of the foil using a scraper to form the desired slurry coating layer on the surface of the foil.
[0089] In one exemplary embodiment, such as Figure 4 As shown, Figure 4 This is a schematic flowchart of the slurry coating layer coating step in another embodiment; S120 involves coating the slurry onto the surface of the foil to form a slurry coating layer on the surface of the foil, specifically including the following steps:
[0090] S121. Determine a foil material that matches the polarity of the slurry and lay the foil material flat on the panel.
[0091] It is understandable that the polarity of the foil and the slurry are matched to prepare an electrode sheet of the corresponding polarity. The panel is used to support the foil to achieve uniform coating of the slurry; in some embodiments, a smooth and flat rigid panel, such as a glass panel, can be selected to allow the foil to be laid flat, avoiding the problem of wrinkles or warping of the foil due to unevenness of the panel, which would affect the uniformity of the slurry coating layer.
[0092] S122. Apply the slurry to the surface of the foil to form a slurry coating layer on the surface of the foil with a thickness equal to the preset coating thickness.
[0093] It should be noted that the surface of the formed slurry coating layer meets the preset flatness requirements to avoid affecting the structural regularity of subsequent electrode material samples due to unevenness of the slurry coating layer surface. The preset flatness requirements need to be determined adaptively according to actual testing needs, and are not specifically limited here.
[0094] The thickness of the slurry coating layer is equal to the preset coating thickness. Determining the preset coating thickness requires considering not only the ease of natural separation between the slurry coating layer and the foil during the drying stage, but also the mechanical strength requirements when peeling off the electrode material sample. This ensures that after the slurry coating layer cures and detaches from the foil surface, it remains intact during the subsequent peeling stage (i.e., completely removing the cured slurry coating layer from the foil surface). This avoids problems such as sample breakage due to excessive thickness or uneven drying and difficulty in interface separation due to excessive thickness. Preferably, the preset coating thickness is 3000μm~7000μm; for example, the preset coating thickness can be 3000μm, 4000μm, 5000μm, 6000μm, or 7000μm.
[0095] The following is a detailed explanation of the preset coating thickness setting:
[0096] Please see Figure 5 ( Figure 5 In the diagram, 10 represents foil, 11 represents hollow sampling tube, and 12 represents slurry coating layer. Figure 5 The slurry coating layer 12 shown on the right is a thin slurry coating layer, for example, with a thickness of 200 μm. With a thin slurry coating layer, the volume shrinkage due to solvent evaporation during drying is small, and the shrinkage stress can be evenly distributed within the slurry coating layer 12. Simultaneously, the contact interface between the thin slurry coating layer and the foil 10 is tighter, and the van der Waals forces and the mechanical interlocking effect between the slurry particles and the foil surface are stronger and more dominant (i.e., shrinkage stress F). 应力 Not large enough, overall cohesive force F 结合力 (pointing to the contact interface), shrinkage stress F 应力 Insufficient to overcome interfacial adhesion, therefore difficult to peel off. From Figure 5 It can be seen that the shrinkage stress F at a certain point on the interface of the thin paste coating layer is... 应力 Less than the total bonding force F 结合力 Overall F 合 Downward movement makes it difficult to peel off the thin paste coating.
[0097] Please continue reading. Figure 5 , Figure 5 The slurry coating layer 12 shown on the left is a thick slurry coating layer, for example, with a thickness of 4000 μm. The thick slurry coating layer experiences large and uneven shrinkage stress, creating an internal separation driving force. When the thick slurry coating layer dries, the surface solvent evaporates much faster than the bottom layer, causing the surface layer to shrink first, followed by the bottom layer, resulting in a significant shrinkage difference and shear stress. Furthermore, the total volume shrinkage of the thick slurry coating layer is much greater than that of the thin slurry coating layer, significantly increasing the accumulated total shrinkage stress. When the stress exceeds the interfacial bonding force between the slurry coating layer and the foil 10, it will push the slurry coating layer 12 to separate from the foil 10. Figure 5 It can be seen that the shrinkage stress F at a certain point on the interface of the thick slurry coating layer is...应力 As it accumulates and increases, when it exceeds the total binding force F... 结合力 When the critical value is reached, the population F 合 Upward movement promotes localized peeling.
[0098] It is evident that the increased stiffness of the thick slurry coating layer contributes to exacerbating the separation trend: after curing, the stiffness of the thick slurry coating layer is significantly increased (unlike the slight deformation that occurs with the foil when the thin slurry coating layer is applied). Therefore, the internal stress generated during the drying process cannot be released through deformation and can only be transferred to the interface between the slurry coating layer and the foil, further increasing the tendency of the slurry coating layer and the foil to separate.
[0099] Furthermore, considering that after drying, a hollow sampling tube is needed to completely peel the cured slurry coating from the foil, if the electrode material sample is too thin, the peeling force generated during the peeling process may cause the sample to break or its edges to tear. Please refer to [link to relevant documentation]. Figure 6 ( Figure 6 In the diagram, 10 represents the foil material and 12' represents the cured slurry coating layer. Figure 6 It can be seen that the cured thick paste coating can withstand greater F. 剥离力 It can be completely peeled off from the surface of foil 10; however, the cured thin paste coating cannot withstand a larger F. 剥离力 It is very easy to break during the peeling process from the surface of foil 10.
[0100] The slurry coating method provided in the above embodiments, by determining a foil material whose polarity matches that of the slurry, ensures good contact and stable adhesion between the slurry and the foil material. This allows the foil material to be laid flat on a smooth, flat panel, facilitating uniform slurry coating and avoiding the problem of wrinkles or warping of the foil material due to uneven panel surfaces, which affects the uniformity of the slurry coating layer. During the coating stage, by setting a reasonable preset coating thickness, it is ensured that when the hollow sampling tube is subsequently embedded in the slurry coating layer for drying, the slurry coating layer inside the tube utilizes the stress generated by dehydration shrinkage to achieve natural peeling from the foil interface. Simultaneously, it ensures that the cured slurry coating layer inside the tube can withstand greater peeling force during the peeling process, thus completely peeling off from the foil surface and avoiding problems such as breakage and boundary damage.
[0101] In one embodiment, S200 presses the hollow sampling tube into the slurry coating layer to obtain a slurry coating layer with the hollow sampling tube embedded, specifically including: pressing the hollow sampling tube into the slurry coating layer according to a preset pressing speed and a preset pressing angle until the hollow sampling tube contacts the surface of the foil.
[0102] The preset pressing speed refers to the speed at which the hollow sampling tube is pressed into the slurry coating layer; the preset pressing speed is less than or equal to 1 mm / s; preferably, the preset pressing speed is 1 mm / s to ensure that the slurry is smoothly filled into the inner cavity of the hollow sampling tube, avoiding slurry splashing, air bubbles being drawn in, or damage to the slurry coating layer structure caused by pressing too fast, while avoiding pressing too slowly, which would result in low pressing efficiency.
[0103] The preset pressing angle refers to the angle between the pressing direction and the surface of the foil used to coat the slurry. Preferably, the preset pressing angle is 90°, that is, the hollow sampling tube is pressed vertically into the slurry coating layer to ensure that the slurry is evenly filled into the inner cavity of the hollow sampling tube.
[0104] The hollow sampling tube has a press-in end; the press-in end may, but is not limited to, adopting an arc structure or a chamfered structure, and no specific limitation is made here. The press-in end is used to guide the hollow sampling tube to be smoothly pressed into the slurry coating layer, reduce the pressing resistance, prevent the slurry from being squeezed out or generating air bubbles, and ensure that the slurry is evenly filled into the inner cavity of the hollow sampling tube.
[0105] In one example embodiment, an automatic pressing device is used to smoothly press the hollow sampling tube into the slurry coating layer at a preset pressing speed and preset pressing angle until the pressed end of the hollow sampling tube contacts the surface of the foil, thereby obtaining a slurry coating layer with the hollow sampling tube embedded in it. This ensures that the inner cavity of the hollow sampling tube is fully and uniformly filled with slurry, laying the foundation for obtaining electrode material samples with regular structure and clear boundaries in the future.
[0106] It should be noted that this application does not specify the number of hollow sampling tubes pressed into the slurry coating layer. For example, multiple hollow sampling tubes can be pressed into the slurry coating layer using the above-described pressing method to obtain multiple electrode material samples and verify the consistency between them. When determining the pressing site, it is necessary to avoid pressing at the edge of the slurry coating layer as much as possible to prevent uneven thickness of the slurry coating layer at the edge or the influence of boundary effects, which could reduce the integrity or consistency of the electrode material samples.
[0107] In the above embodiments, the hollow sampling tube is pressed into the slurry coating layer at a preset pressing speed and a preset pressing angle. This can effectively avoid problems such as uneven cross-section and structural damage of the slurry coating layer inside the hollow sampling tube caused by excessive speed or tilting angle during the pressing process. This ensures the uniformity of the slurry coating layer inside the hollow sampling tube and lays the foundation for obtaining electrode material samples with regular structure and clear boundaries in the future.
[0108] Based on the above embodiments, the drying process of this application will be described in detail below.
[0109] Please continue reading. Figure 2Based on the above description of the stress on the slurry coating layer inside the hollow sampling tube during the drying stage, it can be concluded that the radial traction force F 牵引力 This originates from the adhesive force between the slurry coating layer and the sidewall of the tube. In practical applications, it has been found that the radial traction force F provided by the hollow sampling tube... 牵引力 The effectiveness depends on the initial solids content of the slurry and the contact time: the lower the initial solids content of the slurry (e.g., less than 50% initial solids content in the slurry coating) and the longer the contact time, the greater the radial traction force F that the hollow sampling tube can provide. 牵引力 The more pronounced the effect, the more likely it is to pull the slurry towards the tube wall, potentially forming a concave sample resembling a "crater." Furthermore, if the initial solids content of the slurry is extremely low, its high fluidity may prevent the formation of the desired slurry coating layer, thus affecting the insertion of the hollow sampling tube.
[0110] Therefore, for slurry coatings with low initial solid content (such as negative electrode slurry coatings), pre-drying can be performed first to increase their solid content before pressing into the hollow sampling tube. Of course, pressing in too late may prevent insertion because the slurry coating has been completely cured. Therefore, a reasonable pre-drying time needs to be set to ensure that the slurry coating has not been completely cured after pre-drying, so that the hollow sampling tube can be successfully pressed in.
[0111] Based on the above, it is clear that the timing of inserting the hollow sampling tube and the drying timing are related to the initial solid content of the slurry coating. The following details the drying methods for slurry coatings with different initial solid contents. It should be noted that the initial solid content mentioned in this application refers to the solid content of the slurry coating before drying during the coating stage. It is understood that the solid content of the slurry coating gradually increases with the extension of drying time during the drying process.
[0112] It should be noted that due to differences in slurry formulation and homogenization process, the ratio of solvent to other components in the slurry varies, resulting in slurry coatings with different initial solid contents. Slurry coatings with different initial solid contents exhibit differences in dehydration rate, shrinkage characteristics, and curing time during the drying process. Therefore, it is necessary to adjust the drying process and the timing of inserting the hollow sampling tube accordingly to ensure the integrity of the electrode material sample and the accuracy of the test results.
[0113] Case 1: The initial solids content of the slurry coating is greater than or equal to 50%. For example, the initial solids content of the slurry coating without drying treatment is in the range of 50% to 70%; alternatively, the initial solids content of the slurry coating is 50%, 55%, 60%, 50%, 65%, or 70%.
[0114] For scenario one, in S300, the slurry coating layer with the embedded hollow sampling tube undergoes a drying process, including the following steps:
[0115] Step 1: Under a preset drying environment, the slurry coating layer with the hollow sampling tube embedded is pre-dried for a first preset time using a first drying temperature.
[0116] The preset drying environment can be a temperature- and humidity-controlled drying device or drying chamber, used to provide stable drying conditions for the slurry coating layer, ensuring uniform dehydration and curing of the slurry. The drying parameters of the preset drying environment (such as temperature and time) can be flexibly set according to the characteristics of the slurry and process requirements. In an exemplary embodiment, the preset drying environment can be a non-vacuum drying chamber with the blower function turned off. The reason is that although turning on the vacuum can lower the boiling point of the solvent, very few gas molecules are available for heat exchange, and heat radiation from the heat source and heat conduction from the contact bottom surface play a major role, which may lead to uneven heating of the slurry. Using a non-vacuum dryer can effectively avoid the above problems. At the same time, by turning off the blower function of the non-vacuum drying chamber, it is possible to avoid the slurry surface drying too quickly due to the blower, while the internal solvent cannot be discharged in time due to the long evaporation time, resulting in solvent accumulation and defects such as cracks and pores.
[0117] The first drying temperature and the first preset time can be set according to the slurry type and the drying parameters (such as temperature and time) of the coating drying process on the production line, and are not specifically limited here. For example, the range of the first drying temperature can be 50℃~90℃; preferably, the first drying temperature can be 50℃, 60℃, 70℃, 80℃ or 90℃; the range of the first preset time can be 0.5h~3h; preferably, the first preset time can be 0.5h, 1h, 1.5h, 2h, 2.5h or 3h.
[0118] Step 2: Raise the temperature to the second drying temperature and use the second drying temperature to dry the pre-dried slurry coating layer containing the hollow sampling tube until the slurry coating layer inside the hollow sampling tube is cured.
[0119] The second drying temperature can also be set according to the type of slurry and the drying parameters of the coating drying process of the production line (such as temperature, time, etc.), and is not specifically limited here; for example, the range of the second drying temperature can be 100℃~120℃; preferably, the second drying temperature can be 100℃, 105℃, 110℃, 115℃ or 120℃.
[0120] It should be noted that when using the second drying temperature, the corresponding drying time ranges from 2 hours to 6 hours, for example, it can be 2 hours, 3 hours, 4 hours, 5 hours, or 6 hours, which is related to the thickness of the slurry coating, the initial solid content, and the type of solvent. The curing refers to the complete evaporation of the solvent in the slurry coating, resulting in the complete detachment of the slurry coating from the foil surface inside the hollow sampling tube.
[0121] For example, for a slurry coating layer with an initial solid content of 50% or more, the hollow sampling tube is pressed into the slurry coating layer directly according to the pressing method described in the above embodiment to obtain a slurry coating layer with the hollow sampling tube embedded. The slurry coating layer with the hollow sampling tube embedded is placed in a non-vacuum drying oven with the blower function turned off. The slurry coating layer with the hollow sampling tube embedded is first pre-dried for a first preset time (e.g., 1 hour) using a first drying temperature (e.g., 75°C). The first drying temperature (e.g., 75°C) is then increased to a second drying temperature (e.g., 110°C). The pre-dried slurry coating layer with the hollow sampling tube embedded is then dried (e.g., dried for 3 hours) using the second drying temperature (e.g., 110°C) until the slurry coating layer inside the hollow sampling tube is cured and completely detached from the foil surface.
[0122] In the above embodiments, for a slurry coating layer with an initial solid content of 50% or more, the slurry coating layer with an embedded hollow sampling tube is moved into a preset drying environment, and the slurry coating layer with the embedded hollow sampling tube is subjected to gradient drying using a first drying temperature and a second drying temperature in sequence. This can effectively prevent problems such as sedimentation caused by the migration of conductive agent with solvent during the drying process, and at the same time ensure that the slurry coating layer completes physical curing under the constraint of the side wall of the hollow sampling tube, so as to maintain the initial homogeneous distribution state of the conductive agent inside the sample.
[0123] Scenario 2: The initial solids content of the slurry coating is less than 50%. For example, the initial solids content of the slurry coating that has not been dried is in the range of 30% to 50%, such as 45%.
[0124] For scenario two, the slurry coating layer needs to be pre-dried before the hollow sampling tube is pressed into it. Specifically, in one embodiment, step S200 involves pressing the hollow sampling tube into the slurry coating layer to obtain a slurry coating layer with the hollow sampling tube embedded, which includes the following steps:
[0125] Step 1: Under a preset drying environment, the slurry coating layer is pre-dried for a second preset time using a third drying temperature to obtain a pre-dried slurry coating layer.
[0126] The limitations of the preset drying environment can be referred to the limitations mentioned above, and will not be repeated here. The third drying temperature and the second preset time can be set according to the type of slurry and the degree of slurry curing, etc., and are not specifically limited here; for example, the value range of the third drying temperature can be 70℃~80℃; preferably, the second drying temperature can be 70℃, 75℃ or 80℃. The value range of the second preset time can be 1h~2h; preferably, the second preset time can be 1h, 1.5h or 2h.
[0127] Understandably, due to the low initial solids content and excessive fluidity of the slurry, a stable slurry coating layer may not form directly, thus affecting the smooth insertion of the hollow sampling tube. Therefore, by pre-drying the slurry coating layer at a third drying temperature under a preset drying environment for a second preset duration, the solids content of the slurry coating layer can be appropriately increased, allowing it to initially set, thereby ensuring that the hollow sampling tube can be smoothly inserted into the pre-dried slurry coating layer.
[0128] Step 2: Press the hollow sampling tube into the pre-dried slurry coating layer until the hollow sampling tube contacts the surface of the foil.
[0129] It should be noted that, in this embodiment, the method of pressing in the hollow sampling tube can be referred to the description above, and will not be repeated here.
[0130] Based on the embodiment of the above-mentioned second situation, in S300, the slurry coating layer embedded with the hollow sampling tube is dried, including: in a preset drying environment, the slurry coating layer embedded with the hollow sampling tube is dried at a fourth drying temperature until the slurry coating layer inside the hollow sampling tube is cured.
[0131] The fourth drying temperature is higher than the third drying temperature. The fourth drying temperature can be set according to the slurry type and the drying parameters (such as temperature and time) of the coating drying process on the production line, and is not specifically limited here. For example, the range of the fourth drying temperature can be 100℃~120℃; preferably, the fourth drying temperature can be 100℃, 105℃, 110℃, 115℃, or 120℃. It should be noted that when using the fourth drying temperature, the corresponding drying time ranges from 4h to 5h, for example, it can be 4h, 4.5h, or 5h, which is related to the thickness of the slurry coating layer, the initial solid content, and the type of solvent.
[0132] For example, for a slurry coating layer with an initial solid content of less than 50%, the slurry coating layer on the surface of the foil needs to be placed in a non-vacuum drying oven with the blower function turned off. The slurry coating layer is pre-dried for a second preset time (e.g., 1 hour) using a third drying temperature (e.g., 75°C) to obtain a pre-dried slurry coating layer with a solid content higher than the initial solid content. The pre-dried slurry coating layer is then removed from the non-vacuum drying oven, and a hollow sampling tube is pressed into the pre-dried slurry coating layer according to the pressing method described in the above embodiment until the pressed end of the hollow sampling tube contacts the surface of the foil. The entire slurry coating layer with the hollow sampling tube is then moved into a non-vacuum drying oven with the blower function turned off, and the slurry coating layer with the hollow sampling tube is dried (e.g., 3 hours) using a fourth drying temperature (e.g., 110°C) until the slurry coating layer inside the hollow sampling tube is cured and completely detached from the surface of the foil.
[0133] In the above embodiments, for slurry coatings with an initial solid content of less than 50%, before pressing into the hollow sampling tube, the slurry coating is pre-dried for a second preset time under a preset drying environment and at a third drying temperature to obtain a pre-dried slurry coating. This can appropriately increase the solid content of the slurry coating, allowing it to initially stabilize, thus ensuring that the hollow sampling tube can be smoothly pressed into the pre-dried slurry coating. The hollow sampling tube is then pressed into the pre-dried slurry coating until it contacts the surface of the foil, obtaining a slurry coating with the hollow sampling tube embedded. Further, under a preset drying environment, the slurry coating with the embedded hollow sampling tube is dried at a fourth drying temperature until the slurry coating inside the hollow sampling tube is cured. This avoids excessive shrinkage of the slurry due to radial traction force from the tube wall caused by direct drying when the initial solid content is too low, resulting in a concave sample with a ring-shaped depression, which would affect the structural regularity of the electrode material sample and the accuracy of the resistivity test results.
[0134] It should be noted that the drying temperatures set above must be designed to accurately simulate the ambient temperature of the actual coating oven to prevent abnormal adhesive migration. This ensures that the microstructure of the electrode material sample remains consistent with that of the actual electrode and that the resistivity test results accurately reflect the electrode material performance under actual production conditions.
[0135] In one embodiment, based on the above embodiment, S300 specifically includes the following steps:
[0136] Step 1: Dry the slurry coating layer with the hollow sampling tube embedded.
[0137] Step 2: Cool the dried slurry coating layer containing the hollow sampling tube to a preset temperature.
[0138] The preset temperature can be room temperature, for example, the preset temperature range can be 20°C to 30°C, or optionally, the preset temperature can be 25°C, to ensure that the electrode material sample is fully cooled and shaped, providing a stable sample state for subsequent peeling operations.
[0139] Step 3: Using a hollow sampling tube, peel off the slurry coating layer inside the hollow sampling tube from the surface of the foil to obtain an electrode material sample.
[0140] It is understood that the aforementioned peeling refers to the complete separation of the solidified and cooled slurry coating layer inside the hollow sampling tube from the surface of the foil.
[0141] For example, the dried slurry coating layer with the hollow sampling tube embedded is transferred into a desiccator for cooling and shaping until the temperature of the slurry coating layer drops to room temperature. A suitable peeling force is then applied to the hollow sampling tube so that the slurry coating layer inside the hollow sampling tube is peeled off from the surface of the foil, thereby obtaining an electrode material sample.
[0142] It is understandable that, because this application controls the thickness of the slurry coating layer within the range of 3000μm to 7000μm during the coating stage, it can ensure that the obtained electrode material sample has higher rigidity. This ensures that it has sufficient mechanical strength to withstand the peeling force during the peeling stage, thus avoiding problems such as breakage or edge damage during the peeling process.
[0143] Based on the above embodiments, two methods for measuring the resistivity of electrode materials are provided below.
[0144] In the first embodiment, S400 performs resistivity measurement on the electrode material sample to obtain resistivity test results, specifically including the following steps:
[0145] A preset pressure is applied to the electrode material sample, and the resistivity of the electrode material sample is measured simultaneously during the compression process to obtain the resistivity test results.
[0146] The resistivity test results include the relationship between the resistivity of the electrode material sample and the pressure. A preset pressure is used to simulate the compaction state of the electrode in an actual battery; the preset pressure can range from 800 kg to 1500 kg; preferably, the preset pressure can be 1000 kg.
[0147] It should be noted that the preset pressure applied to the electrode material sample in this application may, but is not limited to, comply with international standards, material design specifications, and the actual pressure requirements of the workshop process. The specific pressure value can be flexibly set according to the material type, formulation characteristics, and target compaction density to ensure that the resistivity test results can truly reflect the electrode material performance under actual production conditions.
[0148] In some possible embodiments, a measuring device that combines compaction and resistivity measurement functions can be used to ensure that resistivity data can be acquired in real time and synchronously during the pressurization process, thereby accurately obtaining the corresponding relationship between the resistivity of the electrode material sample and pressure. In some embodiments, the measuring device can also visualize the change in resistivity of the electrode material sample during compression.
[0149] It should be noted that this embodiment may, but is not limited to, using the four-probe method for resistivity measurement; the principle of the four-probe method can be understood from relevant documents in the prior art, and will not be elaborated further.
[0150] Alternatively, in this embodiment, the resistivity of the compacted sample can be obtained after the compression process is completed, according to actual testing requirements.
[0151] In the first embodiment, by applying a preset pressure to the electrode material sample and simultaneously measuring the resistivity of the electrode material sample during the compression process, the resistivity evolution law of the electrode material during the compression process can be dynamically captured, and the corresponding relationship between resistivity and pressure can be obtained, thereby comprehensively characterizing the change characteristics of the electrode material under different compaction states.
[0152] In the second embodiment, S400 performs resistivity measurement on the electrode material sample to obtain resistivity test results, specifically including the following steps:
[0153] Step 1: Apply a preset pressure to the electrode material sample to obtain a compacted sample.
[0154] The limitations of the preset pressure can be referred to in the above description, and will not be repeated here; compacted sample refers to the final state of the electrode material sample after being compacted under preset pressure and reaching the target compaction density.
[0155] Step 2: Measure the resistivity of the compacted sample to obtain the resistivity test results.
[0156] The resistivity test results include the resistivity of compacted samples. Compacted sample resistivity refers to the resistivity value of the electrode material sample under a specific compaction state, used to reflect the conductivity of the electrode material at the actual electrode compaction density. The resistivity measurement method can be, but is not limited to, the four-probe method; no specific limitation is made here.
[0157] In the second embodiment, by performing pressurization and measurement in separate steps, the operation is simple and does not require complex measuring equipment, thus reducing the complexity of the test and the cost of equipment; at the same time, it is convenient to quickly compare the performance differences of different homogenization processes and different formulations of electrode materials.
[0158] In one embodiment, the hollow sampling tube is made of quartz. Quartz, primarily composed of SiO2, is chemically stable and does not react with the slurry, thus avoiding sample contamination or performance distortion caused by the interaction between the material and the slurry components. Quartz has an extremely low coefficient of thermal expansion, offering unparalleled thermal stability compared to common plastics, glass, and steel, ensuring dimensional stability during drying and guaranteeing the forming accuracy of the electrode material sample. Furthermore, quartz is transparent, facilitating observation of the contact state between the slurry coating and the tube wall, the liquid film distribution, and deformation phenomena during drying. This allows for timely adjustment of process parameters, improving the controllability and consistency of sample preparation.
[0159] And / or, the wall thickness of the hollow sampling tube is 0.1mm to 1mm; ensuring structural strength while possessing excellent indentation and slurry cutting ability. Preferably, the wall thickness of the hollow sampling tube is 0.1mm, 0.5mm, or 1mm. In some embodiments, the wall thickness of the hollow sampling tube can be determined according to the initial solid content of the slurry coating layer; for example, if the initial solid content is greater than or equal to 50%, a thinner wall thickness is preferred, such as between 0.1mm and 0.3mm. Optionally, the wall thickness can be 0.1mm, 0.2mm, or 0.3mm, because the thinner the wall thickness of the hollow sampling tube, the sharper its indentation end, making it easier to cut into the slurry coating layer and reducing indentation resistance. If the initial solid content is less than 50%, any value between 0.1mm and 1mm can be used, for example, 0.5mm.
[0160] And / or, the height of the hollow sampling tube is 16mm~32mm; preferably, the height of the hollow sampling tube is 16mm, 20mm or 32mm; to ensure that while meeting the sampling function, the ease of operation and structural stability are taken into account, and to avoid difficulties in pressing in or uneven drying due to excessive height, or insufficient sampling volume or inconvenience in operation due to insufficient height.
[0161] And / or, the hollow sampling tube has a press-in end, and the hollow sampling tube has a chamfer at the press-in end; the chamfer structure is specifically manifested in that the wall thickness of the press-in end gradually decreases along the axial direction towards the end; by setting a chamfer at the press-in end, the pressing resistance can be reduced, guiding the hollow sampling tube smoothly into the slurry coating layer, avoiding the slurry being squeezed out or generating air bubbles during the pressing process, ensuring that the slurry is uniformly filled into the inner cavity of the hollow sampling tube; at the same time, it can avoid the phenomenon of uneven slurry cut surface or incomplete cutting during pressing. Preferably, the chamfer set at the press-in end can be a wedge-shaped structure.
[0162] And / or, the hollow sampling tube has a cylindrical structure with open ends. The hollow sampling tube has axial and circumferential dimensions, and its wall has a through-hole area. Multiple through-holes are provided within the through-hole area. These multiple through-holes are arranged in multiple rows at uniform intervals along the axial direction of the hollow sampling tube, and the through-holes in each row are arranged at uniform intervals along the circumferential direction of the hollow sampling tube. Please refer to [link / reference]. Figure 7 ( Figure 7 In the middle, 11 represents a hollow sampling tube. Figure 7A schematic diagram of a hollow sampling tube is shown. By providing through-hole areas in the tube wall and ensuring that multiple through-holes are evenly spaced in multiple rows along the axial direction of the hollow sampling tube, and that the through-holes in each row are evenly spaced along the circumference of the hollow sampling tube, a uniformly distributed air channel can be formed, generating a balanced "chimney effect" in all directions. This allows the drying airflow to circulate evenly inside and outside the hollow sampling tube, ensuring that all areas of the slurry coating are heated uniformly and that the solvent evaporation rate is balanced. This avoids problems such as local over-drying or under-drying and differences in sample surface formation caused by uneven airflow distribution, thereby improving the structural uniformity and surface smoothness of the electrode material sample and ensuring the accuracy and repeatability of resistivity test results.
[0163] In some embodiments, the hollow sampling tube has a pressing end for pressing in the slurry coating layer, and the distance between the through-hole area and the pressing end is greater than the thickness of the slurry coating layer (the thickness of the slurry coating layer is 3000 μm to 7000 μm). For example, the distance between the through-hole area and the pressing end can be in the range of 8 mm to 10 mm; optionally, the distance between the through-hole area and the pressing end can be 8 mm, 9 mm, or 10 mm. This ensures that the through-hole area is located above the slurry coating layer, preventing the slurry from overflowing from the through-hole during the pressing stage and ensuring that the slurry fully fills the inner cavity of the hollow sampling tube. Simultaneously, during the drying stage, a stable airflow channel is formed between the through-hole area and the slurry coating layer, allowing solvent vapor to be discharged uniformly and smoothly, thereby ensuring that the electrode material sample is uniformly dried and fully cured.
[0164] In some embodiments, the average diameter of the plurality of through holes is 0.2 mm to 0.3 mm; preferably, the average diameter of the plurality of through holes is 0.2 mm, 0.25 mm or 0.3 mm.
[0165] And / or, on the inner wall of the hollow sampling tube, the area with through holes is S1, and the area without through holes is S2, where 0.1 ≤ S1 / (S1+S2) ≤ 0.7. S1+S2 refers to the total area of the hollow sampling tube wall. The area with through holes refers to the area occupied by the through-hole region; the area without through holes refers to the area occupied by the solid tube wall region. The ratio of the through-hole region to the solid tube wall region can be flexibly adjusted according to the initial solid content of the slurry, the type of solvent, and the drying conditions: for slurries with high initial solid content and good drying conditions, the proportion of the through-hole region or the pore diameter can be appropriately reduced; for slurries with low initial solid content and high solvent evaporation, the proportion of the through-hole region or the pore diameter can be appropriately increased to enhance the "chimney effect," promote timely discharge of solvent vapor, and avoid condensation backflow diluting the sample surface, affecting the uniformity of the surface conductive agent distribution, and thus affecting the accuracy and reliability of the resistivity test results. This ensures the structural uniformity of the electrode material sample and the accuracy of the resistivity test results.
[0166] In some embodiments, the inner diameter of the hollow sampling tube is 0 μm to 20 μm larger than the inner mold cavity size of the measuring device described in the above embodiments; preferably, the inner diameter of the hollow sampling tube is 10 μm larger than the inner mold cavity size of the measuring device described in the above embodiments. This design can compensate for the shrinkage deformation of the slurry coating layer inside the hollow sampling tube during the drying process, ensuring that the size of the cured electrode material sample is more closely matched with the inner mold cavity of the measuring device, avoiding excessively large or small fitting gaps caused by sample shrinkage, thereby ensuring stable positioning and uniform pressure of the sample in the measuring device, and improving the accuracy and repeatability of resistivity testing. It can be understood that the outer diameter of the hollow sampling tube = the inner diameter of the hollow sampling tube + the wall thickness of the hollow sampling tube × 2. The limitation of the wall thickness of the hollow sampling tube can be referred to the limitation above, and will not be repeated here.
[0167] In some embodiments, the coating thickness of the slurry coating layer is 3000μm~7000μm; this ensures that the resulting electrode material sample has a more robust structure and can adapt to most testing environments. Simultaneously, the electrode material sample also has a pressure-holding function, which can prevent electrode breakage during the removal process after compaction or during four-probe insertion testing.
[0168] In some embodiments, the slurry coating layer can be a positive electrode slurry coating layer or a negative electrode slurry coating layer, which improves the universality and practicality of the electrode material resistivity measurement method.
[0169] In one embodiment, based on the above embodiments, this application also provides a method for screening battery slurry homogenization processes, including the following steps:
[0170] Step 1: Various slurries to be tested were prepared using different homogenization processes.
[0171] It should be noted that the differences between different homogenization processes lie in the different homogenization conditions, such as differences in parameters such as stirring speed, stirring time, dispersion temperature, feeding sequence, or initial solid content.
[0172] Step 2: For each slurry to be tested, the electrode material resistivity measurement method described in any of the above embodiments is used to obtain the target resistivity test results of a preset number of electrode material samples to be tested, and the homogenization process evaluation index of the slurry to be tested is determined based on the preset number of target resistivity test results.
[0173] The preset quantity needs to be set according to the actual screening requirements, and no specific limit is made. The electrode material sample to be tested is prepared based on the slurry to be tested. The method for determining the electrode material sample to be tested can be referred to the description above, and no specific limit is made here.
[0174] Homogenization process evaluation indicators are used to quantify the quality of the homogenization process corresponding to the tested slurry. These indicators may include, but are not limited to, multiple sub-indicators, such as mean, standard deviation, and relative standard deviation, to comprehensively evaluate the quality of the homogenization process corresponding to the tested slurry from different perspectives.
[0175] For example, for each type of slurry to be tested, a preset number of electrode material samples to be tested are obtained according to the method described in the above embodiments; the resistivity of the electrode material samples to be tested is measured to obtain the resistivity test results corresponding to each electrode material sample to be tested; statistical analysis is performed on the resistivity test results corresponding to all electrode material samples to be tested (e.g., calculating the standard deviation, mean, relative standard deviation, etc.) to obtain the homogenization process evaluation index corresponding to the slurry to be tested.
[0176] Understandably, by statistically analyzing the resistivity test results of each electrode material sample, the concentration trend and dispersion of the resistivity of the electrode material under the homogenization process can be comprehensively characterized, thereby objectively assessing the stability and reliability of the homogenization process and avoiding process misjudgment caused by accidental errors in a single measurement.
[0177] Step 3: Determine the optimal homogenization process evaluation index that meets the preset screening conditions from multiple homogenization process evaluation indexes.
[0178] The preset screening conditions need to be set according to actual needs and are not specifically limited here. For example, when the evaluation indicators for homogenization processes include standard deviation, mean, and relative standard deviation, these three values can be compared comprehensively. For instance, priority can be given to screening homogenization processes whose mean is within the target range and whose standard deviation and relative standard deviation are both less than the corresponding preset thresholds, in order to balance the superior conductivity of the electrode material and batch-to-batch consistency. Through multi-dimensional comprehensive comparison, the optimal homogenization process can be scientifically screened from various homogenization processes, providing a comprehensive basis for process optimization in actual production.
[0179] Step 4: Determine the optimal homogenization process as the homogenization process corresponding to the optimal homogenization process evaluation index.
[0180] In one specific embodiment, taking the homogenization process evaluation indicators including standard deviation, mean, and relative standard deviation as an example, four different homogenization processes were used to prepare four types of slurries to be tested. For each slurry to be tested, three sets of electrode material samples to be tested were prepared using the methods described in the above embodiments. Each electrode material sample was placed in a measuring device that combines compaction and resistivity measurement functions to measure the resistivity of the electrode material. The maximum pressure was set to 74 MPa (under the condition of a compaction pressure of 1000 kg and a compaction diameter of 13 mm, the pressure can be calculated to be approximately 74 MPa according to the pressure formula P=F / S). The target resistivity test results corresponding to the three sets of electrode material samples to be tested were obtained (in this embodiment, the target resistivity test results are the resistivity of the compacted sample). Then, based on the target resistivity test results, the homogenization process evaluation indicators of the corresponding slurry to be tested, namely standard deviation, mean, and relative standard deviation, were calculated to obtain the test data shown in Table 1. Among them, negative-1-A (graphite-based negative electrode slurry), negative-1-B (graphite-based negative electrode slurry), positive-2-B (ternary positive electrode slurry), and positive-2-A (ternary positive electrode slurry) are four different slurries prepared by four different homogenization processes. Each one represents a batch (or a homogenization process scheme), and three parallel samples (i.e., three groups of electrode material samples to be tested) are tested within each group.
[0181] Table 1
[0182]
[0183] As shown in Table 1, the mean resistivity of -1-A and -1-B is similar, but the standard deviation and relative standard deviation (RSD) of -1-B are both lower, indicating that the resistivity of the electrode material is more consistent under this homogenization process. Therefore, the homogenization process corresponding to -1-B is preferred. For -2-B and -2-A, the standard deviation, mean, and relative standard deviation of -2-A are all lower, indicating that this homogenization process not only has better consistency but also better dispersion of the conductive agent inside the electrode material. Therefore, the homogenization process corresponding to -2-A is preferred.
[0184] The graphite-based negative electrode slurry (by mass percentage, graphite 51.65%, binder (polyvinylidene fluoride 1.65%), conductive agent (carbon black 1.65%), solvent (N-methylpyrrolidone 45.05%), initial solid content 54.95%) has a low average resistivity, consistent with the theoretical expectation of good intrinsic conductivity of graphite. In contrast, the ternary positive electrode slurry (lithium nickel cobalt manganese oxide 62.83%, binder (polyvinylidene fluoride 1.32%), conductive agent (carbon black 1.64%), solvent (N-methylpyrrolidone 34.21%), initial solid content 65.79%) has poor conductivity, hence its average resistivity is higher than that of the negative electrode slurry, and the dispersion state of the conductive agent has a more significant impact on its resistivity.
[0185] It should be noted that slurry resistivity can also be used for quality monitoring in daily production. For example, the standard specifies that the resistivity of the positive electrode slurry for a certain battery model should be ≤7Ω. If cm, then the resistivity is higher than 7Ω. The slurry of cm, such as the slurry "positive-2-B" in Table 1 above, can be intercepted during the homogenization stage to prevent the flow of unqualified products, take measures in advance, and reduce internal quality loss costs.
[0186] In one specific embodiment, the tester can obtain a short cylindrical electrode material sample that fits the inner cavity of the measuring device (which has both compaction and resistivity measurement functions) by adjusting parameters such as the slurry coating thickness, the size (inner diameter, wall thickness) of the hollow sampling tube, and the drying temperature and time. After testing, the short cylindrical electrode material sample, having undergone compaction at 74 MPa (higher pressures can also be used, depending on the slurry compaction standard requirements), has a further reduced height, a smoother and denser surface, and a more regular shape that approximates a standard cylinder, sufficiently demonstrating the effectiveness of the compaction process. Simultaneously, the measuring device has real-time resistance display and pressure holding functions, enabling clear observation of the dynamic changes in resistivity of the electrode material sample during gradual compression, thereby obtaining a complete correspondence between resistivity and pressure changes, providing a basis for optimizing the homogenization process and setting electrode rolling process parameters; please refer to... Figure 8 A measuring device that combines compaction and resistivity measurement functions is used to apply a preset pressure to the electrode material sample and simultaneously measure the resistivity of the electrode material sample during the compression process. Figure 8 The diagram shows a resistance variation curve and a compaction density variation curve; in the resistance variation curve, the horizontal axis represents pressure (MPa) and the vertical axis represents resistance (Ω); in the compaction density variation curve, the horizontal axis represents pressure (MPa) and the vertical axis represents compaction density (g / cm³). 3 ),from Figure 8 The resistivity change characteristics of the electrode material sample during the gradual compression process can be clearly observed.
[0187] It should be noted that this application can directly evaluate the slurry quality before the formal preparation of the electrode sheet, that is, before at least four processes in the battery process, such as coating, drying, rolling, and die cutting. This avoids the waste cost of a large amount of material after it is made into electrode sheets or even battery cells, thereby enabling enterprises to reduce costs and increase efficiency, while improving the overall product quality and safety performance of the industry and creating significant social benefits.
[0188] Furthermore, this application only requires small-batch homogenization to prepare electrode material samples for testing, which can evaluate the impact of different formulations and homogenization schemes, while eliminating interference from differences in subsequent process parameters such as coating, drying, rolling, and die-cutting. In an increasingly competitive market environment, this will significantly shorten the cell development and process development cycle, reduce R&D costs, create profit margins and technological advantages for enterprises, and accelerate the iterative upgrading of battery technology in my country.
[0189] Furthermore, this application is highly implementable, using conventional testing equipment that is easy to implement and cost-effective. In contrast, the wet process provided in related technologies, if using an online solution, typically requires modification of the production line equipment structure, making it difficult for small and medium-sized enterprises to implement. Therefore, the wet process cannot possess the aforementioned irreplaceable comprehensive advantages.
[0190] It should be understood that although the steps in the flowcharts of the embodiments described above are shown sequentially according to the arrows, these steps are not necessarily executed in the order indicated by the arrows. Unless explicitly stated herein, there is no strict order restriction on the execution of these steps, and they can be executed in other orders. Moreover, at least some steps in the flowcharts of the embodiments described above may include multiple steps or multiple stages. These steps or stages are not necessarily completed at the same time, but can be executed at different times. The execution order of these steps or stages is not necessarily sequential, but can be performed alternately or in turn with other steps or at least some of the steps or stages of other steps.
[0191] Those skilled in the art will understand that all or part of the processes in the methods of the above embodiments can be implemented by a computer program instructing related hardware. The computer program can be stored in a non-volatile computer-readable storage medium, and when executed, it can include the processes of the embodiments of the above methods. Any references to memory, databases, or other media used in the embodiments provided in this application can include at least one of non-volatile memory and volatile memory. Non-volatile memory can include read-only memory (ROM), magnetic tape, floppy disk, flash memory, optical memory, high-density embedded non-volatile memory, resistive random access memory (ReRAM), magnetic random access memory (MRAM), ferroelectric random access memory (FRAM), phase change memory (PCM), graphene memory, etc. Volatile memory can include random access memory (RAM) or external cache memory, etc. By way of illustration and not limitation, RAM can take many forms, such as Static Random Access Memory (SRAM) or Dynamic Random Access Memory (DRAM). The databases involved in the embodiments provided in this application may include at least one type of relational database and non-relational database. Non-relational databases may include, but are not limited to, blockchain-based distributed databases. The processors involved in the embodiments provided in this application may be general-purpose processors, central processing units, graphics processing units, digital signal processors, programmable logic devices, quantum computing-based data processing logic devices, artificial intelligence (AI) processors, etc., and are not limited to these.
[0192] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this application.
[0193] The embodiments described above are merely illustrative of several implementation methods of this application, and while the descriptions are specific and detailed, they should not be construed as limiting the scope of this patent application. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of this application, and these all fall within the protection scope of this application. Therefore, the protection scope of this application should be determined by the appended claims.
Claims
1. A method for measuring the resistivity of electrode materials, characterized in that, The method includes: S100: Obtain a paste coating layer disposed on the surface of the foil; S200. Press the hollow sampling tube into the slurry coating layer to obtain a slurry coating layer with the hollow sampling tube embedded. S300. The slurry coating layer embedded with the hollow sampling tube is dried to solidify the slurry coating layer inside the hollow sampling tube and detach it from the surface of the foil to obtain an electrode material sample. S400. Based on the electrode material sample, the resistivity of the electrode material is measured to obtain the resistivity test results.
2. The method according to claim 1, characterized in that, S100 specifically includes: S110. Obtain the slurry; the slurry is prepared by a preset homogenization process; S120. The slurry is coated onto the surface of the foil to form the slurry coating layer on the surface of the foil.
3. The method according to claim 2, characterized in that, S120 specifically includes: S121. Determine a foil material that matches the polarity of the slurry, and lay the foil material flat on the panel; S122. The slurry is coated onto the surface of the foil to form a slurry coating layer on the surface of the foil with a thickness equal to a preset coating thickness; the preset coating thickness is 3000μm~7000μm.
4. The method according to claim 1, characterized in that, S200 specifically includes: The hollow sampling tube is pressed into the slurry coating layer at a preset pressing speed and preset pressing angle until the hollow sampling tube contacts the surface of the foil.
5. The method according to any one of claims 1 to 4, characterized in that, When the initial solid content of the slurry coating is greater than or equal to 50%, in step S300, the drying process of the slurry coating with the embedded hollow sampling tube includes: Under a preset drying environment, the slurry coating layer with the hollow sampling tube is pre-dried for a first preset time using a first drying temperature. The temperature is raised to a second drying temperature, and the pre-dried slurry coating layer containing the hollow sampling tube is dried using the second drying temperature until the slurry coating layer inside the hollow sampling tube is cured.
6. The method according to claim 1, characterized in that, When the initial solid content of the slurry coating is less than 50%, S200 specifically includes: Under a preset drying environment, the slurry coating layer is pre-dried for a second preset time using a third drying temperature to obtain a pre-dried slurry coating layer. The hollow sampling tube is pressed into the pre-dried slurry coating layer until the hollow sampling tube contacts the surface of the foil.
7. The method according to claim 6, characterized in that, In S300, the drying process of the slurry coating layer embedded with the hollow sampling tube includes: Under a preset drying environment, the slurry coating layer with the hollow sampling tube is dried using a fourth drying temperature until the slurry coating layer inside the hollow sampling tube is cured. The fourth drying temperature is higher than the third drying temperature.
8. The method according to claim 1, characterized in that, The S300 specifically includes: The slurry coating layer with the embedded hollow sampling tube is dried. The dried slurry coating layer containing the hollow sampling tube is cooled to a preset temperature. The slurry coating layer located inside the hollow sampling tube is peeled off from the surface of the foil to obtain the electrode material sample.
9. The method according to claim 1, characterized in that, The S400 specifically includes: A preset pressure is applied to the electrode material sample, and the resistivity of the electrode material sample during the compression process is measured simultaneously to obtain the resistivity test result; the resistivity test result includes the corresponding relationship between the resistivity of the electrode material sample and the pressure. Alternatively, the S400 specifically includes: A preset pressure is applied to the electrode material sample to obtain a compacted sample; The resistivity of the compacted sample is measured to obtain the resistivity test result; the resistivity test result includes the resistivity of the compacted sample.
10. The method according to claim 1, characterized in that, The hollow sampling tube is made of quartz; and / or, The wall thickness of the hollow sampling tube is 0.1 mm to 1 mm; and / or, The height of the hollow sampling tube is 16mm~32mm; and / or, The hollow sampling tube has a press-in end, and the hollow sampling tube has a chamfer at the press-in end.
11. The method according to claim 1, characterized in that, The hollow sampling tube has a cylindrical structure with openings at both ends. The hollow sampling tube has axial and circumferential directions. The tube wall of the hollow sampling tube is provided with a through-hole area. Multiple through holes are provided in the through-hole area. The multiple through holes are evenly spaced in multiple rows along the axial direction of the hollow sampling tube. The through holes in each row are evenly spaced along the circumferential direction of the hollow sampling tube. The hollow sampling tube has a pressing end for pressing into the slurry coating layer, and the distance between the through-hole area and the pressing end is greater than the thickness of the slurry coating layer.
12. The method according to claim 11, characterized in that, The average diameter of the plurality of through holes is 0.2 mm to 0.3 mm; and / or, The inner wall of the hollow sampling tube has an area of S1 where the through hole is provided and an area of S2 where the through hole is not provided, where 0.1≤S1 / (S1+S2)≤0.
7.
13. A method for screening battery slurry homogenization process, characterized in that, The method includes: Various slurries to be tested were prepared using different homogenization processes; For each of the slurries to be tested, the electrode material resistivity measurement method according to any one of claims 1 to 12 is used to obtain a preset number of target resistivity test results for the electrode material samples to be tested, and based on the preset number of target resistivity test results, the homogenization process evaluation index of the slurry to be tested is determined. The optimal homogenization process evaluation index that meets the preset screening conditions is determined from multiple homogenization process evaluation indexes. The homogenization process corresponding to the evaluation index of the optimal homogenization process is determined as the optimal homogenization process.